ADVANCES FOR THE INTEGRATED MANAGEMENT OF FRUIT WEEVIL OF Myrciaria dubia (Kunth) McVaugh (Conotrachelus dubiae O'Brien), IN A FLOODPLAIN OF THE AMAZON RIVER, PERU - PAREDES DÁVILA, Elvis Javier (2020)
The increase in the population of camu camu pests (Myrciaria dubia) has been affecting 50-80 % of the fruit in plantations. The most important pest is the fruit weevil (Conotrachelus dubiae), whose larva attacks the fruit, eating the seed and causing rotting of the pulp. The objective of this study was to validate technologies for the integrated management of C. dubiae in floodplain plantations. Two treatments were compared: T1=Control (without IPM), 10 plants without any management or control practices. And T2=Integrated management (with IPM), 10 plants with joint application of cultural, ethological and biocidal control techniques. A completely randomized experimental design was applied, with 10 repetitions, evaluating the number of fruits produced, the percentage of green fruits, fallen and damaged by C. dubiae, as well as the fruit yield. A slight superiority of the MIP treatment was found in the percentage of fruits damaged by C. dubiae, in immature stage 2 (12.7 %), we assume that this lower damage is due to the interaction of the control methods used, which negatively affected the cycle life of C. dubiae. The stage of greatest damage begins in the transition from immature fruit 2 to green fruit, reaching the maximum point in green fruit (88.7 % without IPM and 90.1 % with IPM). The fruit yield was higher without IPM (15 612.3 g /pl in immature fruits 2 and 648.7 g/pl in green fruits). The application of IPM was not efficient in the control of C. dubiae in floodplain restinga soil, not favoring the fruit yield of camu camu.